Dual‐Ion Batteries: High Oxidation Potential ≈6.0 V of Concentrated Electrolyte toward High‐Performance Dual‐Ion Battery (Adv. Energy Mater. 25/2021). Issue 25 (8th July 2021) - Tong, Xiaoyu; Ou, Xuewu; Wu, Nanzhong; Wang, Haiyan; Li, Jin; Tang, Yongbing
Abstract : In article number 2100151, Yongbing Tang and co‐workers develop a 4.0 m LiFSI/TMS high‐concentration and high‐voltage electrolyte, which shows significantly suppressed gas formation and enhanced anion intercalation reversibility under high working voltages. Based on this electrolyte system, the dual‐ion battery (DIB) exhibits much improved electrochemical performance. This work provides an effective approach to improve the performance of DIBs.